A44 FATTY ACID COMPOSITION OF THE MEDITERRANEAN DIET PROTECTS AGAINST SPONTANEOUS COLITIS IN THE MUCIN-2 DEFICIENT MURINE MODEL. (4th March 2021) - Haskey, N; Ye, J; Barnett, J A; Birnie, B W; Verdugo Meza, A A; Ghosh, S; Gibson, D L
Abstract: Background: A Mediterranean diet (MD) has been proven efficacious in reducing inflammation in many chronic conditions, mediated by the interaction between diet, the gut microbiota and the immune system. The role of the MD as a dietary management strategy in the management of colitis requires further elucidation. While high fat diets have been shown to result in dysbiosis, our lab has clarified that the type of fat, not total calories derived from fat, predict gut dysbiosis and immunity in murine models of colitis. The n-6 polyunsaturated fatty acids (PUFA) promote colitis, however monounsaturated fatty acids (MUFA) protect against colitis. We hypothesize that a blend of fats, similar to the MD (high MUFA, low n-6 PUFA) will promote gut health beneficial to colitis. Aims: Using a murine model of chronic intestinal inflammation, the aim of this study was to investigate the effects of dietary fatty acids on colitis by studying dietary fats in isolation from each other, as well as in a fatty acid profile similar to the blend contained in the MD. Methods: Mice lacking the mucin 2 gene (Muc 2 -/- ) were weaned on to a 9-week, high fat (41%), isocaloric, isonitrogenous diet where the fat was derived from corn oil, olive oil, milk fat or a MD fat blend (28% MUFA, 8% SFA, 4% n-6 PUFA, 1% n-3 PUFA). The MD fat blend mimicked the fat profile consumed in the human diet. Disease activity, colon histology, cytokines (serum and colonic expression), cecal short chain fatty acids, intestinal permeability, glucose tolerance and gut microbiota (16S rRNA) were analyzed. Results: Muc 2 -/- fed the MD were protected from developing the most severe form of colitis, showing significantly lower disease activity and the absence of rectal prolapse. Histological damage was more severe in the corn oil and milk fat groups which coincided with an increase in infiltrating inflammatory cells and increased mucosal ulcerations. MD and milk fat diets exhibited enhanced intestinal permeability, glucose tolerance, intestinal alkaline phosphatase compared to the corn oil diet. Lower colonic mRNA levels of pro-inflammatory RELM-ß and IL-6 were also seen in the MD and MF diet in comparison to corn oil diet with the milk fat eliciting unique protective immune responses as evidenced by increased expression of IL-22 and Reg3-γ. Differences in alpha-diversity were seen between the MD and milk fat diets, beta-diversity revealed differences in taxa between diet groups. Conclusions: The fatty acid profile of the MD protects against the development of spontaneous colitis in the Muc2 -/- mouse model. In summary, not all dietary fats aggravate colitis, and some may be beneficial during colitis. A diet low in n-6 PUFA and high in MUFA is recommended. Funding Agencies: CCCCFDR